2013
DOI: 10.1016/j.jpain.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated With Development of TMD and Its Intermediate Phenotypes: The Genetic Architecture of TMD in the OPPERA Prospective Cohort Study

Abstract: Genetic risk factors are believed to combine with environmental exposures and contribute to risk of developing temporomandibular disorder (TMD). In this prospective cohort study, 2,737 people without TMD were assessed for common genetic variation in 358 genes known to contribute to nociceptive pathways, inflammation, and affective distress. During a median follow-up period of 2.8 years, 260 people developed first-onset TMD. Hazard ratios (HRs) were computed as measures of association between 2,924 single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 78 publications
1
67
0
3
Order By: Relevance
“…The current model of the susceptibility for developing TMD includes anatomical, neuromuscular, and psychological factors that operate in parallel, reflecting the concerted effects of genetic and non-genetic etiological factors. [35][36][37][38] The OPPERA project began by recruiting 3,300 healthy women who were followed up for five years with the expectation that about 10% would develop TMD over the course of the study. By having participants respond to psychological questionnaires, questionnaires that describe various aspects of TMD pain, and a number of psychophysical and cardiovascular assays, this project identified non-genetic risk factors for TMD.…”
Section: Pain Genetics: Ongoing Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The current model of the susceptibility for developing TMD includes anatomical, neuromuscular, and psychological factors that operate in parallel, reflecting the concerted effects of genetic and non-genetic etiological factors. [35][36][37][38] The OPPERA project began by recruiting 3,300 healthy women who were followed up for five years with the expectation that about 10% would develop TMD over the course of the study. By having participants respond to psychological questionnaires, questionnaires that describe various aspects of TMD pain, and a number of psychophysical and cardiovascular assays, this project identified non-genetic risk factors for TMD.…”
Section: Pain Genetics: Ongoing Studiesmentioning
confidence: 99%
“…Thus far, SNPs and haplotypes (i.e., a set of jointly inherited SNPs located on the same chromosome) of HTR2A and COMT were documented as associated with TMD. 38 The OPPERA study revealed additional genes as risk factors for TMD, including NR3C1, CAMK4, CHRM2, IFRD1, and GRK5. 38 A GWAS analysis is now underway with that study cohort.…”
Section: Pain Genetics: Ongoing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective cohort study (32), where healthy females underwent experimental pain testing and genetic analysis, demonstrated that enhanced pain sensitivity in healthy adults predicts the development of TMD and that genetic variations affect both pain sensitivity and risk of TMD. A recently proposed model states that the association between genetic factors and TMD development risk are mediated by intermediate phenotypes of psychosocial distress and pain amplification, that interact with exposition to environmental factors to exert its influence (33). So, further studies are warranted to elucidate whether the relation between pain thresholds and non-specific physical symptoms are secondary or predisposing to the presence of chronic TMD pain.…”
Section: Figmentioning
confidence: 99%
“…Genetic factors play a role in the etiology of persistent pain conditions, putatively by modulating underlying processes such as nociceptive sensitivity, psychological well-being, inflammation, and autonomic response (22). Several genetic risk factors for clinical, psychological, and sensory phenotypes associated with TMD onset have been reported (23). Measures of somatic symptoms are reportedly most strongly associated with TMD onset, but perceived stress, previous life events, and negative affect have also been shown to predict TMD incidence (24).…”
Section: Discussionmentioning
confidence: 99%